Methods of teaching the language of profession (on the example of the manual “The Spanish language for Economists of Ecology”) - Yulia Tsarapkina (Ибероамериканские тетради)
The article analyzes the theoretical and practical aspects of the methodology of professionally oriented teaching of the Spanish language on the material of a manual intended for senior students of the bachelor’s degree studying at the faculty of «Applied Economics and Commerce» in the field of preparation “Ecology and Nature Management”.